2017
DOI: 10.1534/genetics.117.202515
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Analysis of the Caenorhabditis elegans Detoxification Response

Abstract: Oxidative damage contributes to human diseases of aging including diabetes, cancer, and cardiovascular disorders. Reactive oxygen species resulting from xenobiotic and endogenous metabolites are sensed by a poorly understood process, triggering a cascade of regulatory factors and leading to the activation of the transcription factor Nrf2 (Nuclear factor-erythroid-related factor 2, SKN-1 in ). Nrf2/SKN-1 activation promotes the induction of the phase II detoxification system that serves to limit oxidative stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 67 publications
0
21
0
Order By: Relevance
“…Upregulation of gst-4 p ::gfp during oxidative stress caused by juglone or depletion of transketolase (TKT-1) is not affected in skn-1a(mg570) mutant animals ( Figures 4A and 4B). wdr-23 negatively regulates skn-1-dependent oxidative stress responses (Choe et al, 2009;Fukushige et al, 2017;Tang and Choe, 2015), but activation of gst-4 p ::gfp by wdr-23(RNAi) is unaltered in skn-1a(mg570) mutants ( Figure 4C). These data indicate that the transcriptional response to oxidative stress does not require SKN-1A.…”
Section: Skn-1a and Skn-1c Are Distinct Transcriptional Regulatorsmentioning
confidence: 94%
See 1 more Smart Citation
“…Upregulation of gst-4 p ::gfp during oxidative stress caused by juglone or depletion of transketolase (TKT-1) is not affected in skn-1a(mg570) mutant animals ( Figures 4A and 4B). wdr-23 negatively regulates skn-1-dependent oxidative stress responses (Choe et al, 2009;Fukushige et al, 2017;Tang and Choe, 2015), but activation of gst-4 p ::gfp by wdr-23(RNAi) is unaltered in skn-1a(mg570) mutants ( Figure 4C). These data indicate that the transcriptional response to oxidative stress does not require SKN-1A.…”
Section: Skn-1a and Skn-1c Are Distinct Transcriptional Regulatorsmentioning
confidence: 94%
“…Expression of truncated SKN-1A[cut] causes strong upregulation of gst-4 p ::gfp, reminiscent of the induction caused by loss of WDR-23, a negative regulator of the skn-1-dependent oxidative stress response (Choe et al, 2009). Analysis of skn-1 gainof-function alleles suggests that inhibition by WDR-23 requires an N-terminal region of SKN-1C (Fukushige et al, 2017;Tang and Choe, 2015). The SKN-1A[cut] protein, which lacks this N-terminal domain, likely drives constitutive activation of gst-4 p ::gfp by escaping inhibition by WDR-23.…”
Section: Conversion Of Glycosylated Asparagine Residues Of Skn-1a To mentioning
confidence: 99%
“…It was reported that exposure of C. elegans to hyperosmotic conditions can also lead to upregulation of the transcriptome of the detoxification pathway genes (glycosyltransferase, cytochrome P450, glutathione S-transferase, and ABC transporters), and their upregulations were partially dependent on SKN-1 (Dodd et al, 2018). skn-1 (RNAi) reduces the expression of many phase II detoxification genes, especially within the gst gene class (Fukushige et al, 2017;Dodd et al, 2018). There are also substances that induce upregulation of the detoxification pathway genes independent of skn-1, for example, t-BOOH (tert-Butyl hydroperoxide), a stable lipid-soluble hydrogen peroxide that attacks lipids and proteins (Oliveira et al, 2009).…”
Section: Metabolism Of Xenobiotics By Cytochrome P450 Pathway Plays Amentioning
confidence: 99%
“…It was reported that exposure of C. elegans to hyperosmotic conditions can also lead to up-regulation of the transcriptome of the detoxification pathway gene (glycosyltransferase, cytochrome P450, glutathione S-transferase, and ABC transporters), and their up-regulation were partially dependent on SKN-1 (Dodd et al, 2018). skn-1 (RNAi) reduces the expression of many phase II detoxification genes, especially within the gst gene class (Dodd et al, 2018;Fukushige et al, 2017).There are also substances that induce upregulation of the detoxification pathway genes independently of skn-1, for example, t-BOOH (tert-Butyl hydroperoxide), a stable lipid-soluble hydrogen peroxide that attacks lipids and proteins (Oliveira et al, 2009). In our study, the expression level of skn-1 do not show significantly difference among different pH conditions ( Supplementary Figure 3).…”
Section: Metabolism Of Xenobiotics By Cytochrome P450 Pathway Play a mentioning
confidence: 99%